2011
DOI: 10.1097/brs.0b013e3181dc8426
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Outcome of a Posterior Approach for Large Ventral Intradural Extramedullary Spinal Cord Tumors

Abstract: Large ventral IDEM spinal cord tumors can be completely removed using a posterior approach and conventional laminectomy. An understanding of the anatomical and growth characteristics of these tumors is extremely important for successful removal. However, this approach should be applied prudently and with a thorough understanding of its limitations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
63
0
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(67 citation statements)
references
References 20 publications
1
63
0
3
Order By: Relevance
“…The tumors were located on the cervical spine in eight patients (ventral, 4; lateral, 3; dorsal, 1) and on the thoracic spine in 12 (ventral, 5; lateral, 6; dorsal, 1) ( Table 3). The largest diameter among the tumors was 15.9 ± 5.0 mm (range [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25], and the dural tail sign was present in 15/20 patients.…”
Section: Patientsmentioning
confidence: 97%
See 2 more Smart Citations
“…The tumors were located on the cervical spine in eight patients (ventral, 4; lateral, 3; dorsal, 1) and on the thoracic spine in 12 (ventral, 5; lateral, 6; dorsal, 1) ( Table 3). The largest diameter among the tumors was 15.9 ± 5.0 mm (range [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25], and the dural tail sign was present in 15/20 patients.…”
Section: Patientsmentioning
confidence: 97%
“…Actually, most surgeons suggest that grade II removal be the standard because of the difficulty and complications of grade I removal [1][2][3][4]. However, one long-term follow-up study (mean 12 years, range [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] showed that the symptomatic recurrence rate was 32 % after Simpson grade II removal [4], which is much higher than the findings from previous reports [1,2,6]. Considering the range of various recurrence rates in previous reports, a study was needed to examine the long-term outcomes after Simpson grade II removal to determine the optimum treatment strategy.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Efforts have been made to improve the surgical technique from extensive laminectomy and facetectomy, to laminoplasty, hemilaminectomy, or even semihemilaminectomy. 5,17,22,35,36,42 Although different surgical techniques have their own indications and contradictions, we should keep in mind that our priority sequence will always be the protection of the spinal cord and its function first, followed by prevention of postoperative spinal instability and deformity, and then minimization of the injuries to ligaments, muscle, and skin, if possible…”
Section: Discussionmentioning
confidence: 99%
“…Spinal meningiomas are separated from the spinal cord by a discrete anatomical barrier, the arachnoid or pia membrane. This allows for removal with a conventional laminectomy in most cases (50). The role of radiotherapy for spinal meningiomas is the same as for intracranial meningiomas.…”
Section: Spinal Canal Meningiomasmentioning
confidence: 99%